Áreas sob curvas: uma sequência didática para o ensino médio - Boldrini, Thiago (2015)
I propose the continuation of the studies of functions on high school by inserting the study of areas under graphics and applications in some subjects such as physics and economics. I present the content as activities to be developed with the teacher's help, the definition of natural logarithm as area under a graph and activities to explore the understanding.